The impact of management accounting practices on value creation among China’s small and medium-sized enterprises - Xiaoli, Yu; Nik Abdullah, Nik Herda (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
There is a limited number of studies that have examined the significance of management accounting practices in facilitating value creation, particularly among companies in China. The main objective of this study was to investigate the influence of management accounting practices on value creation through their techniques among small and medium enterprises (SMEs) in China from the perspective of the Dynamic Capabilities Theory. Additionally, the study aimed to examine the extent to which management accounting practices were utilized. This study employed PLS-SEM to analyze data obtained from 599 valid questionnaires using the stratified sampling technique. The results indicated that management accounting practices, through their techniques, had a substantial impact on value creation within SMEs in China. This study contributes to the growing body of literature on the relationship between management accounting practices and value creation in China’s SMEs. The findings also expand the understanding of the extent of the use of management accounting practices in small and medium-sized enterprises. This research provides empirical evidence of the potential for substantial enhancement of value creation through the adoption of management accounting practices, which can improve competitiveness, ensure business sustainability, and foster long-term performance.